PERANCANGAN BLUEPRINT ANTI-FRAUD PROGRAM UNTUK MEMINIMALISASI RISIKO TERJADINYA FRAUD DI CV. MOGA JAYA - Juan Christanto Hendrawan (CALYPTRA, 2018)
This is a qualitative-explanatory research and is a basic research because the researcher tried to design anti-fraud program in orderto the help company to minimize the risk of fraud occuring in the short and long term. Companies used by researchers is a family business that has a medium business scale (UMKM). UMKM has a huge contribution to the overall Indonesia's GDP with a figure that reached 57% in 60% and continues to grow in the future UMKMs also contribute to the provision of employment in Indonesia with an average employment upto 95% annually over the past five years. ofaverage growth of UMKMs is also always positive. Including the apparel industry. This good growth were not followed by any good news about the internal control of UMKM itslef. Previous research suggest that internal controls built by SMEs are less effective. Another concern states that family business also has an internal control that is not very effective when compared with non-family business because of lack of implementation and excessive trust. A weak internal control. regardless of the lack of scope or implememntation, will make a business vulnerable to fraud with any motivation (four fraud motivations based on fraud diamonds). Therefore, it is very important for an organization to design an Anti-Fraud Programs, althought it is still very limited, and desire to create an effective anti-fraud program in a short time. Therefore, researcher will try to design an effective anti-fraud blueprint program for companies, especially for the income cycle.